COMPARING THE EFFECT OF TWO METHODS OF ANESTHESIA INDUCTION ON CONSCIOUSNESS DURING ORTHOPEDIC SURGERY - Nanaei, Farhad; Adarvishi, Sara; Dastoorpoor, Maryam; Sekhavatpour, Zohre (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: Consciousness during anesthesia is a non-reversible complication that may expose the patient to severe, long-term, emotional injuries and post-traumatic stress. Therefore, this study aimed to compare the effect of two methods of induction maintenance of anesthesia with thiopental sodiumâ€“remifentanil and propofolâ€“alfentanil on consciousness during orthopedic surgery using a bispectral index (BIS) device. Methods: In this triple-blind clinical trial, 111 patients who underwent orthopedic surgery in Dezful Hospital (southwestern Iran) were investigated. Patients were randomly assigned into two groups: The intervention Group Aâ€ received thiopental for the induction of and fentanyl for maintenance and intervention Group Bâ€ received propofol and alfentanil. The patients underwent BIS monitoring before the end of surgery, and the BIS value was recorded. The Brice questionnaire was used to measure the consciousness. The data were analyzed using repeated Measure ANOVA test. Results: In the intervention Groups A and B, the mean BIS score was 63.71 and 60.62 in the first 5 min after surgery, reaching 65.25 and 67.73 60 min after surgery, respectively. The results of repeated measures ANOVA test showed that the mean BIS score was significantly different from the preoperative value (baseline) group during repeated measurements after surgery (5, 10, 15, 30, 40, and 60 min) (p<0.001). According to the Brice questionnaire, the prevalence of hearing loss during surgery showed a statistically significant difference between the two intervention Groups (A and B), and the incidence of hearing during surgery in intervention Group Bâ€ was approximately 3 times higher than intervention Group Aâ€ (odds ratio=3.22, 95% confidence interval: 1.32â€“7.79). Conclusion: The results indicate that none of the induction and maintenance pharmacologic methods have any superiority in terms of optimal depth of anesthesia in patients undergoing orthopedic surgery.